Komisi Pemberantasan Korupsi Pasca Perubahan Undang-undang dalam Perspektif Kelembagaan - Farah Syah Rezah; Andi Tenri Sapada (Universitas Cokroaminoto Yogyakarta, 2026)
The revision of the Corruption Eradication Commission Law explicitly places it as a government institution within the executive branch. Additionally, the establishment of a Supervisory Board with the authority to grant permits for wiretapping, searches, and seizures has sparked debate regarding the limits of the KPK's independence. The issues raised in this study relate to the KPK's position after the amendment of the KPK Law and the KPK's independence as an executive body after the amendment of the KPK Law. The method used in this study is the normative legal method. The research results show that the position of the KPK after the amendment to the law falls within the executive branch of power, while the KPK's independence as an executive institution is now limited because its institutional position is under the administrative control of the government. the KPK can be restored as an independent institution free from interference by any power. In addition, strengthening institutional aspects, proportionate supervision, employe professionalism, and public transparency are key to maintaining the KPK's credibility as the front line in eradicating corruption.